How pastoralists weight future environmental benefits when managing natural resources. Issue 2 (13th October 2020) - Hyman, Amanda A.; Gaoue, Orou G.; Tamou, Charles; Armsworth, Paul R.
Abstract: Natural resource management involves balancing benefits and costs that accrue through time. How individuals and local communities weight such tradeoffs can profoundly influence how they use and conserve resources. Our goal was to understand time preferences of future benefits for goods that are relevant for developing effective conservation strategies. We surveyed >500 Fulani in Benin about their time preferences regarding financial, ecological, and agricultural goods, summarizing these in the form of discount rates. In a discrete‐time, constant annual form, our results were much higher (median: 150%) than values often discussed in literature. These discount rates declined through time; people valued the future more than would be assumed based on constant discounting. Discount rates were higher for financial goods than ecological or agricultural goods. We illustrate how our estimates of discount rates change recommendations for optimal management of forest resource harvesting in the tropics. While members of this grazing community discount future benefits at a high rate, they do so in ways that contrast with conventional economic theory and favor long‐term use of nontimber forest products.